Análise de aspectos qualitativos e sociodemográficos relacionados ao incômodo causado por gases odorantes em ambiente urbano industrializado - Cavalcante, Franciele Ribeiro (2023)
This study aims to identify qualitative factors that interfere with the perception and annoyance caused by odorous in an industrialized urban environment. Surveys were carried out in two periods that differ in the seasonality of meteorological conditions in the study region. Analyzes were performed using the chi-square test for homogeneity, the chi-square test for independence, and binary multivariate logistic regression. The results show that respondents are concerned about air pollution. Respondents perceive different forms of air pollution: pollution due to amount of dust/dust, loss of visibility, and presence of odors. Among respondents who were annoyed due to odors, there was a higher prevalence of being extremely annoyed. The primary sources of odors identified by respondents were the steelmaking and sewage treatment plants. The main impact caused on the respondents' daily lives was to close the windows to avoid the odor. The chi-square test for homogeneity identified significant differences in the responses of the two surveys for variables related to the respondents' profile, perception of air pollution, and perception of odor pollution. The following variables associated with increased chances of feeling highly annoyed with odors were: perception of other forms of air pollution, such as dust and loss of visibility, gender, frequency of perception of male odor, and occurrence history of respiratory problems. This study contributes by identifying qualitative factors that interfere with the reactions of individuals exposed to odorous pollution and allow interested parties (companies, environmental agencies) to plan and implement policies aimed at these particularities to reduce the effects on health and quality of life.